Immunomodulation of endothelial cells induced by macrolide therapy in a model of septic stimulation. Issue 4 (12th October 2021) - Pons, Stéphanie; Arrii, Eden; Arnaud, Marine; Loiselle, Maud; Ferry, Juliette; Nouacer, Manel; Lion, Julien; Cohen, Shannon; Mooney, Nuala; Zafrani, Lara
Abstract: Objectives: Sepsis is defined as the host's inflammatory response to a life‐threatening infection. The endothelium is implicated in immunoregulation during sepsis. Macrolides have been proposed to display immunomodulatory properties. The goal of this study was to analyze whether macrolides can exert immunomodulation of endothelial cells (ECs) in an experimental model of sepsis. Methods: Human ECs were stimulated by proinflammatory cytokines and lipopolysaccharide before exposure to macrolides. ECs phenotypes were analyzed by flow cytometry. Cocultures of ECs and peripheral blood mononuclear cells (PBMCs) were performed to study the ECs ability to alter T‐cell viability and differentiation in the presence of macrolides. Soluble factor production was assessed. Results: ECs act as non‐professional antigen presenting cells and expressed human leukocyte antigen (HLA) antigens, the adhesion molecules CD54, CD106, and the coinhibitory molecule CD274 after septic stimulation. Incubation with macrolides induced a significant decrease of HLA class I and HLA class II HLA‐DR on septic‐stimulated ECs, but did not alter either CD54, CD106, nor CD274 expression. Interleukin‐6 (IL‐6) and IL‐8 production by stimulated ECs were unaltered by incubation with macrolides, whereas Clarithromycin exposure significantly decreased IL‐6 gene expression. In cocultures of septic ECs with PBMCs, neither the proportion of CD4  + , CD8  +  T nor their viability was altered by macrolides. T‐helper lymphocyte subsets Th1, Th17, and Treg polarization by stimulated ECs were unaltered by macrolides. Conclusion: This study reports phenotypic and gene expression changes in septic‐stimulated ECs exposed to macrolides, without resulting in altered immunogenicity of ECs in co‐cultures with PBMCs. In vivo studies may help to further understand the impact of macrolide therapy on ECs immune homeostasis during sepsis. Abstract : This study reports phenotypic and gene expression changes in septic‐stimulated microvascular endothelial cells after exposure to macrolides. Although a significant decrease in cell‐surface human leukocyte antigen (HLA) class I and HLA‐DR expression and in interleukin‐6 (IL‐6) gene expression was observed, these modifications did not result in altered functional response following endothelial cells' interaction with peripheral blood mononuclear cells (PBMCs) regarding T‐lymphocyte viability, cytokine production, or CD4  +  ‐T differentiation.